Pengoptimuman skema logikal pangkalan data hubungan : kajian kes pangkalan data sistem maklumat hidrologi Malaysia - Kurmin, Norazrin (2006)
It is important to ensure that storing, retrieving, and data manipulating could be done efficiently in a database. This research is focused on the data access in Sistem Maklumat Hidrologi Malaysia (SMHM). The main issue that attracts researchers is low execution time in accessing data. The factor that causes the problem is the structure of the database. Besides, there is such a huge amount of data in SMHM database. Hence, this research produces an optimization technique of relational database logical scheme in order to fix the problem. The technique that has been produced is based on equijoin technique in which two entities that hold the same attribute will be joined and also the tuple classification. In addition, query will be analyzed in order to produce a maximum optimal execution. Comparison has been done on the techniques that have been developed and the SMHM cube system which is the previous technique. The results of the research prove that the technique that has been produced could improve the execution time for query processor, and solve the issue that has been discussed.